Życie codzienne urzędnika cesarskiego w świetle wybranych insygniów "Notitia dignitatum" - Wiewiorowski, Jacek (Vox Patrum, 2026)
The text analyzes severel illustrations of Notitia Dignitatum from around 400 AD, which contain the insignia of a few of the top palace officials of the Eastern and Western Roman Empires: comites sacrarum largitionum, comites rerum privatarum and castrenses sacri palatii. The emblems visualize their competences and position within the imperial administration, while also depict objects that they could encounter in their daily lives. Those objects are identified by the author by using more sources and taking into account the findings of other researchers. He concludes that the illustrations in Notitia dignitatum could be beneficial for the study of daily life in late antiquity. All the primary copies of Notitia Dignitatum, which contained the insignia mentioned above, and several copies made on their basis, were considered in the text. Key words Notitia dignitatum;